If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Bx + Gy = Kforx Solving xB + yG = forxK Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1forxK' to each side of the equation. xB + -1forxK + yG = forxK + -1forxK Reorder the terms: -1forxK + xB + yG = forxK + -1forxK Combine like terms: forxK + -1forxK = 0 -1forxK + xB + yG = 0 Add '-1yG' to each side of the equation. -1forxK + xB + yG + -1yG = 0 + -1yG Combine like terms: yG + -1yG = 0 -1forxK + xB + 0 = 0 + -1yG -1forxK + xB = 0 + -1yG Remove the zero: -1forxK + xB = -1yG Combine like terms: -1yG + yG = 0 -1forxK + xB + yG = 0 The solution to this equation could not be determined.
| x+3=z-5 | | 217+x/(13.2-X)(32.8-X)=1.25 | | Ax+Fy=Kforx | | 1.25=217+x/(13.2-X)(32.8-X) | | -12n+6=-10n-2 | | 2(4a-7)+a=76 | | -37-(-43)=x/6 | | 2(4c-1)-6=3c+7 | | -7(t+1)=14 | | -7(t+1)=4 | | 1/2(18x+2)=3(3x-2)-3(x-7) | | 1/2(p+6)=7/2(3-p) | | 3x^2+(k-1)x-2=0 | | 27-19=4(x-6) | | -7x+1=9 | | 30+5y-12=17y-9-3y | | x+23+4x=-22-4x-27 | | -x(x-2)(x+2)(x+2)=0 | | b^12*b^10= | | -0.4x^2+2.2x+4.7=0 | | w^6*w^8= | | 5q^2-2bq-3=0 | | -4x+1=33 | | 2m/5+4=-10/9-3 | | P(2)-10P+22=0 | | 3(z-4)+6= | | -11/7=z-2/3 | | 2log(x-3)-log(x+1)=2 | | k*k^12= | | 4x^2+7x=6 | | a^4-6a^2+5=0 | | 6+2(1+2x)=29-3x |